Unconscious anticipation of the consequences of a disrupted environment: the role of building strategic capabilities - (:unkn) unknown (My University, 2023)
The Covid-19 pandemic provides us with an opportunity to examine what organizations are doing to face and overcome major societal challenges. Our case is an exception in the African context, and allows us to understand through the theoretical corpus of the anticipation discipline how a higher education institution overcame the environmental disruptions caused by the Covid-19 pandemic. We use the grounded theory approach to analyze our data from semi-structured interviews, information and documents and videos found on the institution's website and social networks, with Nvivo software. The results of our analyses show that building the strategic capabilities of organizations can play a decisive role in anticipating environmental disturbances. This finding allows us to suggest the development of digital capabilities, resilience capabilities and innovation capabilities as strategic capabilities for anticipating potential environmental disruptions.
Keywords: African Research